Infection coefficient of Maize streak virus, leafhoppers composition and control using biopesticids and some cultural practices in agro‑ecological zones of Cameroon - Djomo, S.H.; Suh, C.; Mbong, G.A.; Fonkou, T.; Mafouasson, H.A.; Touna, P.; Sounou, A.P.; Fotso Kuate, A.; Nanga, S.N.; Fiaboe, K.; Meseka, S.K.; Menkir, A.; et al. (Springer, 2022)
Maize streak virus (MSV) is a major threat to cereal production, hence food security in sub-Saharan Africa. The virus is spread mainly by insect vectors. The leafhoppers composition and distribution of potential MSV vectors were evaluated, and the performance of various control techniques against the vectors assessed in the major maize production areas of Cameroon. These techniques included the use of botanical extracts of Azadirachta indica A Juss. and Chenopodium ambrosoides L. Mosyakin and Clements, intercropping maize with cassava and soybean, and use of the synthetic insecticides Imidacloprid. The infection coefficient of maize streak disease and the abundance of leafhoppers were assessed in three agro-ecological zones of Cameroon (AEZs) including the Sudano-Sahelian zone (AEZ I), the Western highlands (AEZ III) and the humid forest with bimodal rainfall (AEZ V). Among 15 leafhoppers species recorded, 15 were recorded in AEZ I; 14 in AEZ III and 12 in AEZ V. The most abundant species in each AEZ was Afrosteles distans (Linnavuori) while the least abundant was Aconurella erebus (Distant). Intercropping maize with cassava and maize with soybean significantly reduced the infection coefficient of MSV in the different study zones. Also, phytochemical treatments significantly performed well with neem being the most efficient in the reduction of abundance compared to the other treatments. Thus, the use of the plant extracts and intercropping against leafhopper vectors of MSV effective.